1964
DOI: 10.1111/j.1365-2672.1964.tb04807.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Growth and Fat Formation of Rhodotorula gracilis

Abstract: Summary: The vitamin requirements of Rhodotorula gracilis are satisfied by inclusion in the growth medium of pantothenic acid and thiamine. For maximum growth in the particular medium and with the size of inoculum used in our experiments a concentration of about 10 μg of pantothenate/1 was sufficient but for rapid early growth a higher concentration was beneficial. Pantothenic acid can be replaced by β‐alanine but maximum growth response then occurs only in the presence of asparagine. Either ammonium sulphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

1968
1968
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…As the pH in the culture was not controlled, sharp declines in the culture pH from 6.5 to around 2.5 were observed in all experiments conducted (Figure 2e). This phenomenon could have been caused by one or more of the following: endogenous production of organic acids by the activated sludge microorganisms;23 the release of acid in the culture with use of ammonium sulfate as the nitrogen source due to the preferential assimilation of NH 4+ radical;29 and the formation of carbonic acid due to the dissolution of the CO 2 produced by microorganisms into the culture 30. Although it was previously reported that culture pH values below 3 reduced biomass and lipid production in pure cultures of oleaginous yeasts31 and bacteria,32 the results of this study showed that lipid accumulation in activated sludge occurred even at these very low pH levels, suggesting that some members of wastewater microbial communities are capable of accumulating lipids at these extreme conditions.…”
Section: Resultsmentioning
confidence: 99%
“…As the pH in the culture was not controlled, sharp declines in the culture pH from 6.5 to around 2.5 were observed in all experiments conducted (Figure 2e). This phenomenon could have been caused by one or more of the following: endogenous production of organic acids by the activated sludge microorganisms;23 the release of acid in the culture with use of ammonium sulfate as the nitrogen source due to the preferential assimilation of NH 4+ radical;29 and the formation of carbonic acid due to the dissolution of the CO 2 produced by microorganisms into the culture 30. Although it was previously reported that culture pH values below 3 reduced biomass and lipid production in pure cultures of oleaginous yeasts31 and bacteria,32 the results of this study showed that lipid accumulation in activated sludge occurred even at these very low pH levels, suggesting that some members of wastewater microbial communities are capable of accumulating lipids at these extreme conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely reported that nitrogen-limited growth conditions increase the ratio of lipid to cell dry weight and R. gracilis can be so induced to produce up to 60% of its own weight of fat, thus giving a fat coefficient (g of fat produced/100 g of glucose utilized) of 15.0-21.0 (Enebo, Anderson & Lundin, 1946;Lundin, 1950;Borrow et al, 1961;Allen, Barnard, Fleming & Hollis, 1964).…”
mentioning
confidence: 99%
“…The final cell yields of 196 to 268 g/10 L are considerably higher than other reports of cell yields (3,54,63). The % fat dry wt.…”
Section: L'îhey Permeate Fermentationscontrasting
confidence: 57%
“…In a few cases5 swabs of material were collected in sterile tubes. Sampling sites and the number of organisms isolated from each were: soil [3], rotting tree stump [2], soil edge of Lake LaVerne [3], horse manure [2], lawn soil [3], spoiled milk [1], standing water [1], and a drain of Iowa State University dairy plant [5]. After preliminary studies indicated that the university dairy plant furnished promising organisms, 42 isolates were obtained from two other cheese plants in Iowa.…”
Section: Isolationmentioning
confidence: 99%